Communication roles of iban community structures in rural development projects in Kanowit, Sibu division, Sarawak - Robert Menua, Anak Salleh. (Faculty of Social Sciences, 2008)
The purpose of this study is to examine the effects and consequences of development upon community structures and traditional processes of communication among that community in Kanowit district, Sarawak. The principle presumptive premise of development programmes is newer is better, the development agencies know best, and by whatever strategy development is to be effected-co-optation or intervention-the recipients also are beneficiaries.